Where are you going? Career development and vocational information (2) - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1980)
A film discussing the various career options available to Newfoundland students. Poor audio quality. Minor distortion throughout.